The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1507/endocrj.ej19-0502
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the relationship between glycated hemoglobin A1c and mean glucose levels derived from the professional continuous flash glucose monitoring system

Abstract: Previously, we reported that short-term continuous glucose monitoring (CGM) with the professional iPro2 © CGM device is a good clinical indicator of glycated hemoglobin (HbA1c) levels. However, there was no significant correlation between CGM and HbA1c levels when HbA1c levels were >8.0%. To further investigate this issue, we performed a similar study using the FreeStyle Libre Pro © , a newer device that does not require glucose calibration and allows patients to be examined for up to 14 days. Fifty-nine patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…However, our data showed a weakening of the relationship between HbA1c and a range of glucose parameters on SUEDs versus non‐SUEDs. In most studies from the literature, a linear relationship exists between HbA1c and glycaemic control parameters such as mean SG and time out of range 24,25 . We found that HbA1c was less closely associated with mean SG, time out of range (SG < 3.9 and >10 mmol/L) and time with SG > 10 mmol/L on days when substances were used.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…However, our data showed a weakening of the relationship between HbA1c and a range of glucose parameters on SUEDs versus non‐SUEDs. In most studies from the literature, a linear relationship exists between HbA1c and glycaemic control parameters such as mean SG and time out of range 24,25 . We found that HbA1c was less closely associated with mean SG, time out of range (SG < 3.9 and >10 mmol/L) and time with SG > 10 mmol/L on days when substances were used.…”
Section: Discussionmentioning
confidence: 64%
“…In most studies from the literature, a linear relationship exists between HbA1c and glycaemic control parameters such as mean SG and time out of range. 24,25 We found that HbA1c was less closely associated with mean SG, time out of range (SG < 3.9 and >10 mmol/L) and time with SG > 10 mmol/L on days when substances were used. Also, a dose-dependent effect was observed for those days when alcohol alone was consumed.…”
Section: Discussionmentioning
confidence: 80%
“…This observation emphasizes that the measurement of DM management, with respect to the glycemic control, should not be focused only on the mean of the glycemic values but also on the dispersion of those values around the average. This association is supported by several articles [42][43][44]. A recent study that included over 600 young patients with T1DM showed a positive correlation between SD and HbA1c, indicating that a higher HbA1c leads to poorer glycemic control [42].…”
Section: Discussionmentioning
confidence: 70%
“…Type 2 diabetes mellitus is more common in the elderly. With the increase of the elderly population in recent years, the incidence rate of type 2 diabetes mellitus exhibits an upward trend, so it has become a public health problem endangering people's health [12] . In clinical practice, the pathogenesis of type 2 diabetes mellitus is not completely clear and there is still a lack of means to cure type 2 diabetes mellitus.…”
mentioning
confidence: 99%